Service-learning as a mandatory credit-bearing subject at the Hong Kong Polytechnic University - Chan, Stephen C F; Ngai, Grace; Shek, Daniel T L (International journal of child and adolescent health, 2019)
Many universities have integrated community engagement in their undergraduate programs. At The Hong Kong Polytechnic University, it is compulsory for all students to take at least one 3-credit subject on service-learning (SL). In each SL subject, there are purpose-designed academic teaching, rigorous service and structured assessment components. At full implementation, roughly 4,500 undergraduate students would enroll in around 70 subjects offered by a wide range of departments and faculties across the university. The subjects cover a diverse range of topics, such as digital divide, learning difficulties, engineering design, healthy living environments, orthotics, and eco-tourism. The target beneficiaries are equally diverse, including slum dwellers, disabled people, children with HIV, villagers without water nor electricity, new immigrants, mentally ill patients, ethnic minorities, and children of migrant workers. To date, students have served different groups of clients in Hong Kong, Chinese Mainland, Cambodia, Vietnam, Indonesia, Myanmar, and Rwanda. This chapter outlines the pedagogical design of the program, challenges and strategies for implementation, and the experiences gained so far.